An Update on Childhood-Onset Takayasu Arteritis - Aeschlimann, Florence A.; Yeung, Rae S. M.; Laxer, Ronald M. (Frontiers in Pediatrics, 2022)
Takayasu Arteritis (TAK) is a rare large vessel vasculitis affecting the aorta and its major branches. The heterogeneous and often severe clinical manifestations result from systemic and local inflammation as well as end-organ ischemia. Disease flares are common and contribute to accrued damage over time with significant morbidity and mortality. Newer understanding of the pathogenesis in TAK has paved the way for the use of pathway targeting agents such as tumor necrosis factor (TNF)alpha- or interleuking (IL)-6-inhibitors with improved disease control. Nevertheless, long-term data are lacking, particularly in children; prognosis often remains guarded and the disease burden high. This article aims at providing a comprehensive review of childhood-onset TAK with a focus on recent publications.